Interculturalidad en el sistema educativo peruano - Águila lsuiza, Enith Dalila Del (2006)
Our country has a variety of cultures, which can not be excluded from the education system and therefore have to be included in the educational process, with an education consistent with the context in which they live. This cultural diversity is presented in spaces defined where human groups coexist with different cultural traditions, which leads to attitudes toward cultural diversity are varied and even subsequent intercultural relations in which one is submerged. This process is complex, not unilinear, and depends even part of the context in which the person is, but here just want to point out that there are influences that, despite not being recognized, act however effectively in individual and collective behavior. In this sense, our purpose is to bring awareness how the recognized cultural diversity of our country, both in relations between the different cultures that originate from him, and between them and those of external origin, live in the great concert called globalization. We needed reflection on the quality of these relations, in order to assess whether they have the character of intercultural. The understanding of the various approaches or natures of multiculturalism is the foundation for understanding what implies a possible intercultural education for all Peruvians of this understanding also derive the understanding that, in Peru, education in human rights, peace education, citizenship education, happen to be also intercultural education; given the essentially multicultural character of the country. Our intention is not to point empty, but provide know how the conceptual basis of our legislation has always been at the forefront of developments in this field on the American continent and even in Europe, although the origins of concern intercultural education are different, as will be seen later. This demonstrates ability to reflect indirectly the performance potential that exists in the country, potential, however, requires not only legal support, but political decisions and planning to boost its realization